2014
DOI: 10.1186/1471-2466-14-192
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the cost-effectiveness of targeted therapies for metastatic non-small cell lung cancer (NSCLC)

Abstract: BackgroundNon-small cell lung cancer (NSCLC) imposes a substantial burden on patients, health care systems and society due to increasing incidence and poor survival rates. In recent years, advances in the treatment of metastatic NSCLC have resulted from the introduction of targeted therapies. However, the application of these new agents increases treatment costs considerably. The objective of this article is to review the economic evidence of targeted therapies in metastatic NSCLC.MethodsA systematic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…Furthermore, various international cost-effectiveness studies have assessed the use of EGFR-TKI for individualized first-line or second-line therapy of advanced NSCLC [11,12], with divergent results, ranging from dominant [13] to an incremental cost-effectiveness ratio (ICER) of over US$100,000/QALY [14,15] for the testing strategy. Important causes of this variability may include crosscountry differences and the perspective of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various international cost-effectiveness studies have assessed the use of EGFR-TKI for individualized first-line or second-line therapy of advanced NSCLC [11,12], with divergent results, ranging from dominant [13] to an incremental cost-effectiveness ratio (ICER) of over US$100,000/QALY [14,15] for the testing strategy. Important causes of this variability may include crosscountry differences and the perspective of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis have indicated the efficacy of targeted agents in the treatment of elderly patients with advanced NSCLC (6). Cancer cell migration and invasion are key events in the development, metastasis and reoccurrence of NSCLC, and previous studies have demonstrated the importance of inhibiting growth and metastasis when selecting clinical treatment regimens for NSCLC (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…of all publications includedMeta-AnalysisTime Horizon coveredQuality assessment toolScreening or treatmentClegg, Scott et al 2001 [84]Examines the cost-effectiveness of four of the newer drugs –vinorelbine, gemcitabine, paclitaxel and docetaxel used for treating the most common type of lung cancer (non-small-cell lung cancer).16NO1995–2000appended appraisal questionstreatmentLange, Prenzler et al 2014 [85]review and assess the economic evidence of treatments with targeted agents in advanced: Non-small cell lung cancer19NO2000–2013The Quality of Health Economic Studies (QHES)treatmentBongers, Coupe et al 2012 [86]comparing the new agents docetaxel, paclitaxel, vinorelbine, gemcitabine and pemetrexed, and the targeted therapies erlotinib and gefitinib with one another10NO2001–2010British Medical Journal (BMJ) 35-item checklisttreatmentRaymakers, Mayo et al 2016 [87]cost-effectiveness of lung cancer screening using low-dose computed tomography (LDCT)13NO2000–2014Drummond checklistScreeningMaher, Miake-Lye et al 2012 [88]cost and cost-effectiveness of the different approaches in Treatment of Metastatic Non-Small Cell Lung Cancer22NO1996–2010-treatmentBrown, Pilkington et al 2013[89]Cost-effectiveness of first-line chemotherapy for patients with advanced and/or metastatic NSCLC.6NO1980–201035-item list described by Drummond and JeffersontreatmentCao, Rodrigues et al 2012[90]describing cost-effectiveness of positron-emission tomography(PET) in staging of non–small-cell lung cancer (NSCLC) and management of solitary pulmonary nodules (SPN)18NO1950–2010Quality of Health Economic Studies (QHES)ScreeningBlack, Bagust et al 2006 [58]examine the cost-effectiveness of screening for lung cancer using computed tomography (CT)6NO1994–2005checklist developed by Drummond and colleaguesScreening …”
Section: Resultsmentioning
confidence: 99%